Image quality of ct angiography using model-based iterative reconstruction in infants with congenital heart disease: Comparison with filtered back projection and hybrid iterative reconstruction. Issue 86 (January 2017) - Jia, Qianjun; Zhuang, Jian; Jiang, Jun; Li, Jiahua; Huang, Meiping; Liang, Changhong
Abstract: Purpose: To compare the image quality, rate of coronary artery visualization and diagnostic accuracy of 256-slice multi-detector computed tomography angiography (CTA) with prospective electrocardiographic (ECG) triggering at a tube voltage of 80 kVp between 3 reconstruction algorithms (filtered back projection (FBP), hybrid iterative reconstruction (iDose 4 ) and iterative model reconstruction (IMR)) in infants with congenital heart disease (CHD). Methods: Fifty-one infants with CHD who underwent cardiac CTA in our institution between December 2014 and March 2015 were included. The effective radiation doses were calculated. Imaging data were reconstructed using the FBP, iDose 4 and IMR algorithms. Parameters of objective image quality (noise, signal-to-noise ratio (SNR) and contrast-to-noise ratio (CNR)); subjective image quality (overall image quality, image noise and margin sharpness); coronary artery visibility; and diagnostic accuracy for the three algorithms were measured and compared. Results: The mean effective radiation dose was 0.61 ± 0.32 mSv. Compared to FBP and iDose 4, IMR yielded significantly lower noise ( P  < 0.01), higher SNR and CNR values ( P  < 0.01), and a greater subjective image quality score ( P  < 0.01). The total number of coronary segments visualized was significantly higher for both iDose 4 and IMR than for FBP ( P  = 0.002 and P  = 0.025, respectively), but there was no significant difference in this parameter between iDose 4 and IMR ( P  = 0.397). There was no significant difference in the diagnostic accuracy between the FBP, iDose 4 and IMR algorithms (χ 2  = 0.343, P  = 0.842). Conclusions: For infants with CHD undergoing cardiac CTA, the IMR reconstruction algorithm provided significantly increased objective and subjective image quality compared with the FBP and iDose 4 algorithms. However, IMR did not improve the diagnostic accuracy or coronary artery visualization compared with iDose 4 .